Fear and Hope: The Henoko Base and the Future of Oura Bay - Muzik, Katherine (Asia-Pacific Journal, 2015)
On a sunny September day, last year, I tumbled from a diving boat into the bright clear blue sea of Henoko's Oura Bay, feeling both fear and hope. Would the corals living there still be fine, as they had been during my previous visits in years past? Or would they and other marine life here be suffering and dying from various negative impacts of human behavior (toxic runoff, sedimentation, garbage, ocean acidification, global warming, overfishing, etc.) which are steadily and inexorably killing coral reefs all around the world?